2020
DOI: 10.1021/acs.jpcc.0c06718
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Influence of α-SnWO4 Exposed Facets on Their Photocatalytic Performance for H2 and O2 Evolution Reactions

Abstract: A significant effect of the five major (121), ( 210), ( 111), (200), and (040) exposed facets obtained experimentally for orthorhombic -SnWO 4 material on its performance for photocatalytic water splitting is highlighted from a hybrid DFT-based comprehensive study.Their electronic, redox, and transport characteristics reveal significant anisotropic characters.The specific function of each surface in water oxidation and proton reduction is in direct relationship with the exposed W coordination number. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Very recently, we examined the fundamental characteristics of the five main (210), (121), (040), (200), and (111) facets obtained in synthesized α-SnWO 4 samples. The two experimental (040) and (200) facets are identical to the (010) and (100) ones. The two (210) and (121) facets are made of three-coordinated Sn with four- and five-coordinated W, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, we examined the fundamental characteristics of the five main (210), (121), (040), (200), and (111) facets obtained in synthesized α-SnWO 4 samples. The two experimental (040) and (200) facets are identical to the (010) and (100) ones. The two (210) and (121) facets are made of three-coordinated Sn with four- and five-coordinated W, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison with the Main Facets of Synthesized α-SnWO 4 Samples. Very recently, 64 we examined the fundamental characteristics of the five main (210), ( 121), (040), (200), and (111) facets obtained in synthesized α-SnWO 4 samples. 28−34 The two experimental (040) and ( 200 Interestingly, the similar behavior in the W exposed species coordination number between the (111), (100), and (001) facets as well as in the exposed W coordination number between (121) and (210) facets led to a similarity in the electronic and redox characteristics.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…Zhu et al converted WO 3 particle films to form α-SnWO 4 porous films with a photocurrent of ∼100 μA/cm 2 (1.23 V vs RHE). The above PEC performance is far below the theoretical value (24.4 mA/cm 2 ), which has been assumed to be the poor carrier transport that limits the photogenerated holes arriving at the material surface …”
Section: Introductionmentioning
confidence: 99%
“…Hence, it has become an appealing option over the past few years. Theoretically, Harb et al 14 studied five significant (121), (210), (111), (200), and (040) exposed facets obtained experimentally from a-SnWO 4 using DFT. They found that the (210) and (121) facets are ideal candidates for the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER), whereas the (200) and (111) facets are only active for the HER.…”
Section: Introductionmentioning
confidence: 99%